The Japanese occupation of Malaya and Singapore, 1941-45 : a social and economic history - Kratoska, Paul H. (NUS Press, 2018)
"Japanese forces invaded Malaya on 8 December 1941 and British forces surrendered in Singapore 70 days later. Japan ruled the territory for 3½ years. During this time, early efforts to maintain pre-war standards gave way to a grim struggle for survival as the once-vibrant economy ground to a halt, and residents struggled to deal with unemployment, shortages of consumer goods, sharp price rises, a thriving black market and widespread corruption. People were hungry, dressed in rags, and falling victim to treatable diseases for which medicines were unavailable, and had little reason to hope for better in the future. Drawing on surviving wartime administrative papers, oral sources, intelligence reports and post-war accounts by Japanese officers, this book presents a picture of life in occupied Malaya and Singapore. It shows the impact of war and occupation on a non-belligerent population, and creates a new understanding of the changes and the continuities that underlay the post-war economy and society. The book was first published in 1998 and is now re-issued in a new edition that incorporates information from newly translated Japanese documents and other recent discoveries."